The future urban growth under policies and its ecological effect in the Jing-Jin-Ji area, China. Issue 4 (April 2021) - Li, Nana; Miao, Shiguang; Wang, Yaoting
Abstract: Since 2016, the Chinese government has invoked some policies to make Jing-Jin-Ji (JJJ) a new urban agglomeration. However, there has been no research to study the effect of these new policies on future urban growth. This study assessed part of these new policies on JJJ urban growth in 2020–2050 using SLEUTH model. Then the ecological effects of the urban growth are evaluated. Results showed the policies had nearly no obvious impact on the whole JJJ urban growth, but affected sub-regional (Beijing, Tianjin and Hebei, respectively) urban growth. Under ecological protection in future, the value of ecological service in JJJ would increase to a maximum of 31.7×10 8 Yuan/km 2 in 2031. The ecological elasticity also increased and the ecological risk was strongly reduced around the present urban area. This ecologically sustainable development is critical to the future urban growth, and should be considered more carefully by urban planners and managers. More policies should be evaluated for JJJ urban growth in future work. Abstract : Future urban growth; Government policy; Ecological effect; SLEUTH model; Remote sensing and GIS.